Combined effects of exposure to hypoxia and cool on walking economy and muscle oxygenation profiles at tibialis anterior. Issue 14 (18th July 2019) - Horiuchi, Masahiro; Handa-Kirihara, Yoko; Abe, Daijiro; Fukuoka, Yoshiyuki
ABSTRACT: We investigated combined effects of ambient temperature (23°C or 13°C) and fraction of inspired oxygen (21%O2 or 13%O2 ) on energy cost of walking ( Cw : J·kg −1 ·km −1 ) and economical speed (ES). Eighteen healthy young adults (11 males, seven females) walked at seven speeds from 0.67 to 1.67 m s −1 (four min per stage). Environmental conditions were set; thermoneutral (N: 23°C) with normoxia (N: 21%O2 ) = NN; 23°C (N) with hypoxia (H: 13%O2 ) = NH; cool (C: 13°C) with 21%O2 (N) = CN, and 13°C (C) with 13%O2 (H) = CH. Muscle deoxygenation (HHb) and tissue O2 saturation (StO2 ) were measured at tibialis anterior . We found a significantly slower ES in NH (1.289 ± 0.091 m s −1 ) and CH (1.275 ± 0.099 m s −1 ) than in NN (1.334 ± 0.112 m s −1 ) and CN (1.332 ± 0.104 m s −1 ). Changes in HHb and StO2 were related to the ES. These results suggested that the combined effects (exposure to hypoxia and cool) is nearly equal to exposure to hypoxia and cool individually. Specifically, acute moderate hypoxia slowed the ES by approx. 4%, but acute cool environment did not affect the ES. Further, HHb and StO2 may partly account for an individual ES.